VvEPFL9-1 Knock-Out via CRISPR/Cas9 Reduces Stomatal Density in Grapevine - Clemens, Molly; Faralli, Michele; Lagreze, Jorge; Bontempo, Luana; Piazza, Stefano; Varotto, Claudio; Malnoy, Mickael; Oechel, Walter; Rizzoli, Annapaola; Dalla Costa, Lorenza (Frontiers in Plant Science, 2022)
Epidermal Patterning Factor Like 9 (EPFL9), also known as STOMAGEN, is a cysteine-rich peptide that induces stomata formation in vascular plants, acting antagonistically to other epidermal patterning factors (EPF1, EPF2). In grapevine there are two EPFL9 genes, EPFL9-1 and EPFL9-2 sharing 82% identity at protein level in the mature functional C-terminal domain. In this study, CRISPR/Cas9 system was applied to functionally characterize VvEPFL9-1 in ‘Sugraone’, a highly transformable genotype. A set of plants, regenerated after gene transfer in embryogenic calli via Agrobacterium tumefaciens, were selected for evaluation. For many lines, the editing profile in the target site displayed a range of mutations mainly causing frameshift in the coding sequence or affecting the second cysteine residue. The analysis of stomata density revealed that in edited plants the number of stomata was significantly reduced compared to control, demonstrating for the first time the role of EPFL9 in a perennial fruit crop. Three edited lines were then assessed for growth, photosynthesis, stomatal conductance, and water use efficiency in experiments carried out at different environmental conditions. Intrinsic water-use efficiency was improved in edited lines compared to control, indicating possible advantages in reducing stomatal density under future environmental drier scenarios. Our results show the potential of manipulating stomatal density for optimizing grapevine adaptation under changing climate conditions.